Natural remedies for hypertension: a systematic review - Ahmad Mizher, Hussam Abdeljabar; Mohd Noor, Muhammad Iqbal Hamidullah; Zaini, Syahrir (Elsevier Ltd., 2025)
Hypertension is a chronic condition contributing significantly to global morbidity and mortality. Increasingly, natural remedies are being considered for hypertension management due to their accessibility, lower cost, and fewer perceived side effects compared to conventional medications. This systematic review aimed to evaluate the scientific evidence on the effectiveness and safety of various natural remedies for treating hypertension. The review included remedies such as garlic, celery, hibiscus, hawthorn, and herbal formulations used in Traditional Chinese Medicine, among others. Following the PRISMA guidelines, eligible studies were selected from databases such as Cochrane Library and PubMed, with quality assessed using the SIGN methodology checklist. Eighteen studies were included, totalling 1915 participants. While many studies showed that these remedies effectively reduced blood pressure, no study demonstrated superior effectiveness of natural remedies over conventional antihypertensive medications. Safety profiles were generally favourable, with few minor side effects reported. However, due to limited and variable safety data, further independent, high-quality research is needed to comprehensively evaluate the long-term safety and efficacy of these remedies for hypertension management.